1912
DOI: 10.1084/jem.15.5.516
|View full text |Cite
|
Sign up to set email alerts
|

On the Permanent Life of Tissues Outside of the Organism

Abstract: In two series of experiments made at the end of 1911 and at the beginning of 1912, new techniques were developed with the view of investigating the problem of prolonging indefinitely the life of tissues isolated from the organism. These techniques are far from perfect and will doubtless be modified in the future. But they have already permitted the establishment of new facts. Fragments of connective tissue have been kept in vitro in a condition of active life for more than two months. As a few c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
117
0
12

Year Published

1920
1920
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 428 publications
(129 citation statements)
references
References 0 publications
0
117
0
12
Order By: Relevance
“…He successfully cultivated chicken embryonic cells by using chicken blood plasma, which is readily available,17 and later successfully cultivated mammalian cells as well 18. In 1912, Carrel demonstrated that the long‐term cultivation of the cells that have been obtained from the connective tissues of chick fetuses is possible (for several months) with a periodic exchange of the medium 19. In 1913, he discovered that adding embryonic extract to blood plasma can dramatically increase cellular proliferation and extend the culture period of fibroblasts from the chick embryo heart 20, 21.…”
Section: History Of Cell Culture Mediamentioning
confidence: 99%
“…He successfully cultivated chicken embryonic cells by using chicken blood plasma, which is readily available,17 and later successfully cultivated mammalian cells as well 18. In 1912, Carrel demonstrated that the long‐term cultivation of the cells that have been obtained from the connective tissues of chick fetuses is possible (for several months) with a periodic exchange of the medium 19. In 1913, he discovered that adding embryonic extract to blood plasma can dramatically increase cellular proliferation and extend the culture period of fibroblasts from the chick embryo heart 20, 21.…”
Section: History Of Cell Culture Mediamentioning
confidence: 99%
“…It is easy to imagine the fascination that the idea of the maintenance of a living organ outside the body held for them, as it was believed at the time that the 'freshness' of the explanted organ and the skill of the surgical team were the crucial factors for the success of a transplantation. Burrows and Carrel observed that explants from embryonic chicken hearts placed in nutrient medium would continue pulsating rhythmically for days [4,6]. They also reported that that single cells would become detached from the bulk of the tissue, move actively away from it and grow into the nutrient medium.…”
Section: Brief Historical Overview Of the Attempts To Cultivate Rhythmentioning
confidence: 99%
“…During the 1880s, opposition to his view was expressed by G6tte (1883) and Offprint requests to: T. B. L. Kirkwood by Vines (1889), who founded their criticisms on what can now be seen as largely semantic issues concerning the definitions of cell death and immortality. More important, however, than any theoretical objection to Weismann's hypothesis was the claim by Carrel (1912) and his co-worker Ebeling (1913) that they could culture somatic chicken cells and tissue outside the donor organism indefinitely. This claim, which generated remarkable and sustained popular interest (see review by Witkowski 1980), would almost certainly have suppressed further interest in Weismann's apparently false prediction.…”
Section: Introductionmentioning
confidence: 99%